Exterior of Mahanaleshwar Temple - Temples of India Project Team (Jio Institute, 2024)
The plinth moulding bands like the gajathara (band of elephants) and narathara (moulding containing human figures) are followed by the kakshasana (seat backs). These have vertical walls which are called the vedika (railing) consisting of rectangular slender geometric patterns that are separated by sculptures. Above the vedika is a slender dwarf wall which acts as the resting backrest from the inside. On the exterior, these slender walls have pilaster motifs with figures in between that are framed by circular niches. The kakshasana is the base of the semi-open mandapa (pillared hall) of the temple.